Low Levels of Usual Physical Activity Are Associated with Higher 24 h Blood Pressure in Type 2 Diabetes Mellitus in a Cross-Sectional Study - Alessandra Teixeira Neto Zucatti; Tatiana Pedroso de Paula; Luciana Verçoza Viana; Rafael DallAgnol; Felipe Vogt Cureau; Mirela Jobim Azevedo; Jorge Luiz Gross; Beatriz D. Schaan; Cristiane Bauermann Leitao (Journal of Diabetes Research)
The aim of this study is to evaluate the association between usual physical activity and 24 h blood pressure (BP) profile in people with type 2 diabetes mellitus (DM). This is a cross-sectional study of 151 participants with type 2 DM. Usual physical activity was assessed by step counting and self-reported questionnaire. BP was measured in office and by 24 h ambulatory BP monitoring (ABPM; 24 h, daytime and nighttime). Mean participant age was 61.1 ± 8.4 years, 64% was women, and mean duration of diabetes was 14.3 ± 8.5 years. Ninety-two percent of participants had hypertension, and office BP was 138 ± 18/78 ± 10 mmHg. Inverse correlations were observed between step count and 24 h BP (systolic, r=−0.186; p=0.022), daytime BP (systolic, r=−0.198; p=0.015), and nighttime BP (pulse pressure, r=−0.190; p=0.019). People were categorized into tertiles of daily step count, and the 1st tertile had higher 24 h systolic BP, daytime systolic BP, daytime mean BP, and daytime systolic BP load than those in the other tertiles, even after adjusting for age and HbA1c. Participants with type 2 DM and low levels of physical activity exhibit higher 24 h and daytime systolic ambulatory BP values as compared with those who performed more steps per day, even after adjustments for confounding factors.